(x-7)-(6x+6)=

Simple and best practice solution for (x-7)-(6x+6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-7)-(6x+6)= equation:


Simplifying
(x + -7) + -1(6x + 6) = 0

Reorder the terms:
(-7 + x) + -1(6x + 6) = 0

Remove parenthesis around (-7 + x)
-7 + x + -1(6x + 6) = 0

Reorder the terms:
-7 + x + -1(6 + 6x) = 0
-7 + x + (6 * -1 + 6x * -1) = 0
-7 + x + (-6 + -6x) = 0

Reorder the terms:
-7 + -6 + x + -6x = 0

Combine like terms: -7 + -6 = -13
-13 + x + -6x = 0

Combine like terms: x + -6x = -5x
-13 + -5x = 0

Solving
-13 + -5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + 13 + -5x = 0 + 13

Combine like terms: -13 + 13 = 0
0 + -5x = 0 + 13
-5x = 0 + 13

Combine like terms: 0 + 13 = 13
-5x = 13

Divide each side by '-5'.
x = -2.6

Simplifying
x = -2.6

See similar equations:

| 4x+3y=-40 | | 5x^2+3x-14=0 | | 4s^2+33s+54=0 | | 50=6(k+8)-5 | | (9x-4)(8x+5)= | | a(n)=-14+(n-1)(2) | | 3n+7(1+2n)=24 | | X-3y-8=0 | | 9x-7=17x-2 | | 12=p-2(6p+5) | | x^3-3x^2-6x=20 | | p^2-7p+6= | | -x^2-18=x^2+12x | | -(3+8x)=-51 | | 5x+40=9x-24 | | 4y=456-2x | | a-10=-3 | | 10x^2-4=6x^2+5 | | 3+4=14 | | 3(2n+8)=-18 | | x-4+8x=6x-16 | | y^2-4y+4= | | 2m^2=21m | | -5x^2+16x-3=0 | | 4x^3-27x^2-11x-1=0 | | 4x^2-49= | | -x^2-12x+5=0 | | y=1-x-x^2 | | 3x^2+3x+11=0 | | 35q=-5 | | 3x^2+12x+27=0 | | 65=-4-3(1+3r) |

Equations solver categories